Digital technologies for firms' competitive advantage and improved supply chain performance - M M Hussain Shahadat; Abu Hena Mohammed Yeaseen Chowdhury; Robert Jeyakumar Nathan; Maria Fekete-Farkas (Journal of Risk and Financial Management, 2023)
Supply chain operation is more competitive in a dynamic business environment. Developing supply chain capability is, hence, important for gaining a competitive advantage and overall improved supply chain performance. The purpose of this study is to explore the potential of digital technologies to enhance supply chain performance and for firms to gain competitive advantage through improved supply chain capabilities. This study, through a survey questionnaire, gathered a total of 150 sample data from supply chain executives and managers in the ready-made garments (RMG) industry in Bangladesh. Findings of the study demonstrate that the digital supply chain is a significant contributor to improving the supply chain capabilities of RMG firms, and it subsequently leads to competitive advantage with a direct positive effect on firms' supply chain performance. The findings also indicate that digital technology has a direct effect on supply chain capability and supply chain performance in RMG firms. Based on these empirical findings, the study draws conclusion that digital technology integration in the supply chain would have a positive contribution to supply chain agility and flexibility, which would enable firms to effectively engage supply chain partners in dealing with unexpected situations in business operations. This study contributes to the current literature on digital supply chain capabilities, and it also provides insights for supply chain managers, policymakers, and practitioners in the fields of supply chains, logistics, and business performance.
Keywords: 650; Bangladesh; digitalization; ready-made garments; supply chain agility; supply chain capability; supply chain flexibility; textile industry